An Analysis of the effects of the social, cultural and scientific advances on science fiction writing in the 1930's - Imperial, Romano G. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1988)
This thesis paper tried to give a somewhat detailed account of how environmental factors played a part in influencing the writing of science fiction in the 1930's by giving examples of several popular stories of the time. The paper also gave a brief history of science fiction writing through the ages, and an even briefer account of the historical background of the 1930's. As can be gleaned from the conclusion, the technological, economic and political factors certainly did play a part in many science fiction stories of the time. However, they varied in the extent in which they influenced the author and his writing.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.